2013
DOI: 10.1111/ijfs.12185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high hydrostatic pressure processing on the extraction, retention and stability of anthocyanins and flavonols contents of berry fruits and berry juices

Abstract: Summary Anthocyanins and flavonols are types of phenolic compounds. Previous researches showed that phenolic compounds are relevant to the quality of plant‐derived foods and beverages. Any food‐processing technologies, which can preserve phenolic compounds after processing, should be taken into account for increasing the food quality. High hydrostatic pressure processing (HHPP) is a novel nonthermal process. There are some researches about the effect of HHPP on total phenolic content, total monomeric anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…[8,10] Many studies have shown that HHP can be used in the extraction of biomaterials from plants. [11] HHPP has some advantages such as not requiring any kind of heating process, which can alter biomaterials extracted from plants. [12] It is a well-known issue that during HHPP the solubility increases, as the pressure increases according to the phase behaviour theory [10,13,14] and pressurized cells show increased permeability due to the mass transfer theory.…”
Section: Introductionmentioning
confidence: 99%
“…[8,10] Many studies have shown that HHP can be used in the extraction of biomaterials from plants. [11] HHPP has some advantages such as not requiring any kind of heating process, which can alter biomaterials extracted from plants. [12] It is a well-known issue that during HHPP the solubility increases, as the pressure increases according to the phase behaviour theory [10,13,14] and pressurized cells show increased permeability due to the mass transfer theory.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic assisted extraction of genipin reported the highest yield after 15 min at 10 C (Ramos-de-la-Peña et al, 2014) and these conditions were selected for HPP. Pressure between 130 and 530 MPa was included in our experiments because polysaccharides extraction from Phellinus linteus and anthocyanins and flavonols from berries by HPP was enhanced in the range of 200e600 MPa (Altuner & Tokuş o glu, 2013;Kim & Iwahashi, 2015). Studies about pectinases for pectin hydrolysis during juice recovery from fruits (Braddock, 1981;Pinelo, Zeuner, & Meyer, 2010) suggested the pectinases dosage used in our study.…”
Section: Genipin Liberation By Hpp Combined With Enzymatic Treatmentmentioning
confidence: 99%
“…Non-thermal technologies such as high pressure processing (HPP) are currently studied to preserve foods, while maintaining food texture and flavor or influencing enzymatic reactions. HPP has been used for extraction purposes, and retention and stability of anthocyanins and flavonols of berry fruits have been found (Altuner & Tokuş o glu, 2013). Polysaccharides extraction from Lentinus edodes stems has shown higher yields and shorter extraction time after HPP treatments when compared to conventional thermal methods (Wang, Yu, He, Zhu, & Li, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition, some new potential uses of HHP in food processing are being investigated by several researchers [6][7][8][9][10][11][12][13] and there are several successful applications of HHP in areas besides food processing. [2,3,[14][15][16] One of the successful applications of HHP is the use of this method to increase the percentage of germination, decrease the germination time and improve microbial quality of seeds and sprouts. [17,18] Plant sprouts are accepted as a healthy food since they are a good and inexpensive sources of nutrients.…”
Section: Introductionmentioning
confidence: 99%